Symptomatology and Anatomy of Stemgrooving (Legno Riccio) 1n the Grape Vine - Kriel, G. J. le R.; Orffer, C. J.; Beukman, E. F. (South African Journal of Enology and Viticulture, 2017)
External and anatomical differences between organs affected and unaffected by stemgrooving were studied on the wine grape cultivar Chenin blanc and the table grape cultivars Barlinka and Almeria. Cultivar susceptibility, graft transmissibility as well as the effect of the disease on the percentage of take and growth in: the nursery were studied. The probability of an association with other virus diseases was considered. Abnormal behaviour of the vascular cambium of infected vines gave rise to hypertrophy, hyperplasia, hypoplasia and parenchymatoses in the secondary xylem and phloem. In diseased tissues dift’erentiation of pbeDogen proceeded abnormally deep into the phloem rays. Graft transmission was detected anatomically within six months. The disease was found in all the vine growing districts of the Western Cape. Anatomical.studies showed that the disease had been present for many years. A negative effect on the percentage of t:’tKe and growth in the nursery was, recorded. A probable-relationship with corky bark was indicated anatomically and by indexing with LN33.